2017
DOI: 10.3177/jnsv.63.357
|View full text |Cite
|
Sign up to set email alerts
|

Iron, Hematological Parameters and Blood Plasma Lipid Profile in Vitamin D Supplemented and Non-Supplemented Young Soccer Players Subjected to High-Intensity Interval Training

Abstract: Summary Vitamin D deficiency has been associated with increased risk for cardiovascular disease and anemia. Vitamin D-related changes in lipid profile have been studied extensively but the relationship between vitamin D and lipid metabolism is not completely understood. As both vitamin D and intermittent training may potentially affect iron and lipid metabolism, the aim of the study was to evaluate whether a daily supplementation of vitamin D can modulate the response of hematological and lipid parameters to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 61 publications
1
15
0
Order By: Relevance
“…Area under the curve with high dose anserine (ANS-HD), low dose anserine (ANS-LD), and placebo (PLA) treatments of the following blood biomarkers: Oxidative stress; superoxide dismutase (SOD), catalase (CAT), glutathione disulfide (GSSG), glutathione (GSH), GSH/GSSG ratio, and thiobarbituric acid active reactive substances (TBARS); cell damage; glutamic-oxaloacetic transaminase (GOT), glutamic pyruvic transaminase (GPT), creatine kinase myocardial band (CKMB), and myoglobin ( Anserine's potential for augmenting cell damage repair adaptations may have reflected a preserved WBC ( Figure 5). However, RBC levels showed a small but significant increase in MCV (p < 0.01) and a decrease (~1%) in MCHC (p = 0.001) in ANS-HD compared with ANS-LD and PLA ( Figure 6), which is close to previously reported decreased MCHC following either intense exercise training (~1%-3%) [15] or a high intensity exercise training combined with a vitamin D supplement (~0.7%) [26]. Senescent RBCs are particularly prone to exercise-induced intravascular haemolysis and an associated…”
supporting
confidence: 89%
“…Area under the curve with high dose anserine (ANS-HD), low dose anserine (ANS-LD), and placebo (PLA) treatments of the following blood biomarkers: Oxidative stress; superoxide dismutase (SOD), catalase (CAT), glutathione disulfide (GSSG), glutathione (GSH), GSH/GSSG ratio, and thiobarbituric acid active reactive substances (TBARS); cell damage; glutamic-oxaloacetic transaminase (GOT), glutamic pyruvic transaminase (GPT), creatine kinase myocardial band (CKMB), and myoglobin ( Anserine's potential for augmenting cell damage repair adaptations may have reflected a preserved WBC ( Figure 5). However, RBC levels showed a small but significant increase in MCV (p < 0.01) and a decrease (~1%) in MCHC (p = 0.001) in ANS-HD compared with ANS-LD and PLA ( Figure 6), which is close to previously reported decreased MCHC following either intense exercise training (~1%-3%) [15] or a high intensity exercise training combined with a vitamin D supplement (~0.7%) [26]. Senescent RBCs are particularly prone to exercise-induced intravascular haemolysis and an associated…”
supporting
confidence: 89%
“…Cholecalciferol was the main form of vitamin D that were supplemented in these studies. The duration of supplementation with vitamin D also varied from 3 h to 6 months [40][41][42][43][44][45][46][47][48][49][50][51][52][53].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Different types of vitamin D were used in these studies, four studies received vitamin D fortified food with cholecalciferol [40,[46][47][48], eight studies received oral vitamin D (cholecalciferol) supplements [42,44,45,[49][50][51][52][53] and in one study subjects were supplemented with ergocalciferol and another one with calcitriol [41,43]. The minimum vitamin D dosage was 20 IU and maximum was 500,000 IU according to these studies ( Table 1).…”
Section: Intervention Characteristicsmentioning
confidence: 99%
“…Other clinical trials also found no significant changes in iron indices among healthy adults despite mega-doses of vitamin D3 [24,25]. Jastrzebska and colleagues have even taken into consideration the influence of physical activity and intermittent training since it can potentially affect vitamin D and iron metabolism, yet no significant differences were still found in the hematological parameters (Hb, Hct, and ferritin) of athletes given 5000 IU of vitamin D daily for eight weeks over those who did not receive supplementation [26]. All these previous studies, including the present one, suggest that vitamin D correction is unlikely to improve, if not reduce, iron indices, at least in apparently healthy populations.…”
Section: Discussionmentioning
confidence: 99%